2010
DOI: 10.3892/mmr.2010.338
|View full text |Cite
|
Sign up to set email alerts
|

Down-regulation of the global regulator SATB1 by statins in COLO205 colon cancer cells

Abstract: Abstract. Special aT-rich sequence binding protein 1 (SaTB1) regulates the expression of more than 1,000 genes in tumor cells. SaTB1 expression has been implicated in metastasis, and its silencing results in reduced cancer progression and the reversion of metastatic cells to normal appearance. Therefore, any compound causing down-regulation of SaTB1 expression or activity may be exploited for its therapeutic potential in terms of cancer regression. earlier studies showed that the 3-hydroxy-3-methylglutaryl coe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…These results may suggest that it could be a promising target for novel anticancer drugs. Baicalein and hydrophobic statins were shown to successfully down-regulate the level of SATB1 in breast and colorectal cancer cells respectively, causing a significant decrease in cells’ proliferation and invasion abilities [60,61,127]. The co-delivery of SATB1 shRNA and doxorubicin by using immunoliposomes was shown to have an antitumor effect on gastric cancer cells [111].…”
Section: Discussionmentioning
confidence: 99%
“…These results may suggest that it could be a promising target for novel anticancer drugs. Baicalein and hydrophobic statins were shown to successfully down-regulate the level of SATB1 in breast and colorectal cancer cells respectively, causing a significant decrease in cells’ proliferation and invasion abilities [60,61,127]. The co-delivery of SATB1 shRNA and doxorubicin by using immunoliposomes was shown to have an antitumor effect on gastric cancer cells [111].…”
Section: Discussionmentioning
confidence: 99%
“…Also, miR-7 and miR-155 were shown to be involved in the posttranscriptional regulation of SATB1 gene expression in breast cancer cells [ 24 ]. SATB1 expression in COLO205 colon cancer cells was downregulated by statins via posttranslational modifications of SATB1 protein which led to targeting it for proteolytic degradation [ 25 ]. Dysregulation of hypothetical SATB1 expression-controlling mechanism in colorectal tissue could lead to an aberrant SATB1 expression and result in global, tumor-promoting changes in affected cells.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that ATO plus SATB1 silencing may be a promising therapeutic approach for treating osteosarcomas in which SATB1 is over-expressed, even though more studies are needed to increase its efficiency and decrease adverse reactions. It has also been reported that SATB1 could be down-regulated by the 3-hydroxy-3-methylglutaryl coenzymeA (HMG-CoA) reductase inhibitors (statin drugs) 29 which are widely used to treat hypercholesterolemia. These results provide a practical way to down regulate SATB1, without invoking significant cytotoxicity.…”
Section: Discussionmentioning
confidence: 99%